VISION OF THE FUTURE AND EDUCATION, KEYS TO ASPIRE NATIONAL DEVELOPMENT - Gomez Sanchez Soto, Ruben (2023)
Nations have the right to reach levels of development that mean living conditions so that their citizens can objectively verify the benefits of the democratic system. These benefits, in turn, are the result of building the future; for which, it is necessary that the statesmen who direct their countries, under an appropriate political leadership, and adequate, but with a high certainty of success. For this reason, it was considered appropriate to develop this research analyzing how, why, when, what priority, and other questions used by countries that have achieved success in their government systems. It is for this reason the investigation of the development models of Singapore and the Republic of Korea, countries that in about sixty (60) years have achieved admired and recognized results worldwide. The investigations make it possible to verify that both countries have used planning in stages and phases, that their main leaders built future scenarios based on visions appropriate to their own realities; but in both cases, the commitment to education was a key condition to achieve the skills and capabilities of their human capital. The commitment to education has been evident, and can be verified by the results achieved in the macroeconomic indices monitored by multinational entities. Finally, it is recommended to review this article, and organize research teams that take the different strategic actions, as topics of analysis to develop their own models, but taking the lessons learned achieved.